Exosomes from adipose‐derived mesenchymal stem cells alleviate liver ischaemia reperfusion injury subsequent to hepatectomy in rats by regulating mitochondrial dynamics and biogenesis. Issue 21 (5th October 2021) - Zhang, Qianzhen; Piao, Chenxi; Ma, Haiyang; Xu, Jiayuan; Wang, Yue; Liu, Tao; Liu, Guodong; Wang, Hongbin
Abstract: Hepatic ischaemia reperfusion injury (HIRI) is a major factor leading to liver dysfunction after liver resection and liver transplantation. Adipose‐derived mesenchymal stem cells (ADSCs) have potential therapeutic effects on HIRI. Exosomes derived from ADSCs (ADSCs‐exo) have been widely studied as an alternative of ADSCs therapy. Thus, the aim of this study was to evaluate the potential protective effect and related mechanism of ADSCs‐exo on HIRI subsequent to hepatectomy. Rats were randomly divided into four groups: Sham, I30R+PH, ADSCs and ADSCs‐exo group. After 24 h of reperfusion, liver and serum of the rats were immediately collected. ADSCs‐exo improved liver function, inhibited oxidative stress and reduced apoptosis of hepatocytes in HIRI subsequent to hepatectomy in rats. ADSCs‐exo significantly promoted the recovery of mitochondrial function, markedly increased the content of ATP in the liver tissue, and improved the ultrastructure of mitochondria in hepatocytes. Moreover, ADSCs‐exo significantly increased the expression of OPA‐1, MFN‐1 and MFN‐2 proteins related to mitochondrial fusion, while DRP‐1 and Fis‐1 mRNA and protein expression associated with mitochondrial fission were significantly decreased after the treatment with ADSCs‐exo. In addition, ADSCs‐exo significantly increased the expression of PGC‐1α, NRF‐1 and TFAM genes and proteins related to mitochondrial biogenesis. ADSCs‐exo improves liver function induced by HIRI subsequent to hepatectomy in rats and maintains mitochondrial homeostasis by inhibiting mitochondrial fission, promoting mitochondrial fusion and promoting mitochondrial biogenesis. Therefore, ADSCs‐exo may be considered as a potential promising alternative to ADSCs in the treatment of HIRI subsequent to hepatectomy.